Socioeconomic status and digital inequality: lessons from Cote D'Ivoire. Issue 2 (3rd April 2022) - Kaba, Bangaly; Meso, Peter
ABSTRACT: This study investigates the problem of digital inequality from a socioeconomic perspective by examining if socioeconomic status moderates the impacts of subjective norms and perceived behavioral control on Internet use continuance in a developing country context. The study sheds empirical light on the context of Internet use continuance by demonstrating that mere access to Internet-capable or Internet-connected personal computational devices is not a sufficient precondition for continued Internet use. Rather, Internet Use Continuance is a function of broader economic factors among them socioeconomic status, communal influence, and government influence. The study also reveals that the effect of subjective norms on Internet use continuance differs across socioeconomic groups. Therefore, policymakers ought to consider using specific and targeted mechanisms in bridging digital inequality, particularly in developing country contexts.